ANALYSIS OF THE LEVEL OF MENTAL HEALTH OF WORKERS USING THE BOGOR – JAKARTA ELECTRIC TRAIN TRANSPORTATION WITH WORK PRODUCTIVITY - Aldi Adi Pratama; Faathir Alfath Risdarmawan; Endrika Septya Adilfi (Jurnal Penelitian Keperawatan Kontemporer, 2023)
Background: Mental health in an all-digital world, especially market expansion which tends to increase sharply, especially after the Covid 19 pandemic, is a very important scourge to maintain in increasing work competition capacity. Job competition in terms of career prospects and lifestyle, is something that is seen as elite, because the level of income is categorized as high. However, for workers who continue to target material outputs, without paying attention to mental health, it will result in decreased performance productivity in the field they carry out. Productivity is the ability of employees to achieve certain tasks in accordance with standards, completeness, cost, and speed so that the efficient and effective use of human resources in an organization. Aim: to find out whether the level of mental health of workers in increasing productivity, has a relationship with the mobility of electric rail transportation. Method: This study uses a quantitative approach with the method of regression analysislinear simple. Simple linear regression analysis is an approach method for modeling the relationship between one dependent variable and one independent variable. In regression, the independent variable explains the variableits dependent. In simple regression analysis, the relationship between variables is linear, where changes in variable X will be followed by changes in variable Y permanently. Results: The results of the correlation value between x and y using the help of Microsoft excel 0.792, while the coefficient of determination is 62.8%, and the value of X is the equation Y = -8.13 + 1.17X. Conclusion: The result of the correlation value between x and y can be 0.792 while the coefficient of determination is 62.8%, which means that the x value can explain y of 62.8%, the rest is influenced by other factors. Or you could say valuelevel stress which has a negative impact on mental health problems, affects valuesproductivity as well as the results of the intercept and the value of X with Y = -8.13 + 1.17X.